Translation and paratexts - Kathryn Batchelor (Oxon : Routledge, 2018)
As the 'thresholds' through which readers and viewers access texts, paratexts have already sparked important scholarship in literary theory, digital studies and media studies. Translation and Paratexts explores the relevance of paratexts for translation studies and provides a framework for further research
Keywords: FOREIGN LANGUAGE STUDY Multi-Language; Translating and interpreting; LANGUAGE ARTS & DISCIPLINES Alphabets & Writing Systems